Development of a hybrid (solid state/gas) femtosecond system of multiterawatt peak power; Proceedings International Conference of Ultrafast Optics - High Fields Short Wavelength, Arcachon, august 31 - september 4, 2009 - Aristov A.; Grudtsin Ya.; Ivanov N.; Krokhin O.; Losev V.; Mamaev S.; Mesyats G. A. Gennady Andreyevich; Mikheev L.; Panchenko Yu.; Rastvortseva A.; Ratakhin N.; Sentis M.; et al. (2009, 2009)
В фонде НТБ ТПУ отсутствует